2019
DOI: 10.1371/journal.pone.0224503
|View full text |Cite
|
Sign up to set email alerts
|

Links between meaning in life and physical quality of life after rehabilitation: Mediating effects of positive experiences with physical exercises and mobility

Abstract: BackgroundIndicators of emotional processes (positive experiences with physical exercises) and functional processes (mobility) were previously found to be associated with positive cognitive resources (meaning in life), and the key outcome in the rehabilitation, namely physical quality of life (QOL). Yet, the mediating roles of such processes were not tested. Therefore, this prospective study investigated whether the relationship between meaning in life and physical QOL was mediated by positive experiences with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 36 publications
0
6
0
1
Order By: Relevance
“…This model assumed that those with a similar attributional style for positive life events will produce positive emotion and psychological resources, leading to restoration of hopefulness. Many studies have explored the recovery effects of positive life experiences and cognitive protective factors on hopelessness ( Czekierda et al, 2019 ; Vines & Nixon, 2009 ). However, past literature has not clearly explained how people change the way they appraise events and recover from hopeless situations using interpersonal pathways, however, close relationships were important when residents were on lockdown ( Nair & Appu, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…This model assumed that those with a similar attributional style for positive life events will produce positive emotion and psychological resources, leading to restoration of hopefulness. Many studies have explored the recovery effects of positive life experiences and cognitive protective factors on hopelessness ( Czekierda et al, 2019 ; Vines & Nixon, 2009 ). However, past literature has not clearly explained how people change the way they appraise events and recover from hopeless situations using interpersonal pathways, however, close relationships were important when residents were on lockdown ( Nair & Appu, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…2 7 9 Associations have been found between meaning in life and physical quality of life after rehabilitation. 10 Dolmer and colleagues 8 have noted rehabilitation as a phenomenon connected to life-world perspectives regarding maintenance of daily functions, dignity and the dialectics between fragility and strength. The rehabilitation process is often governed by timelimited goals.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…According to logotherapy theory, meaning in life is the most important personal attribute that protects individuals during challenging life situations (Frankl, 2005). A review of previous investigations with clinical and non-clinical samples (Czekierda et al, 2019; Damásio et al, 2013; Osamika & Asagba, 2019) have revealed that meaning in life is associated with improved quality of life. A meta-analysis also showed that meaning in life is positively associated with physical health (Czekierda et al, 2017).…”
mentioning
confidence: 99%
“…Furthermore, having a sense of meaning in life has been associated with a reduced tendency to engage in EA (Kelso et al, 2020; Yela et al, 2020) and higher quality of life (Czekierda et al, 2019; Damásio et al, 2013; Osamika & Asagba, 2019). Recently, Kelso et al (2020) found that meaning in life altered the relationship between EA and anxiety, such that when the levels of meaning in life are high, the rate of EA predicting anxiety symptoms is reduced.…”
mentioning
confidence: 99%